Pengaruh Kompetensi dan Disiplin Kerja terhadap Kinerja ASN dengan Variabel Mediasi Motivasi Kerja - Zuraini Zuraini; Budi Hasyim (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The performance of Indonesian civil servants (ASN) remains suboptimal, as reflected in the 2023 national BerAKHLAK index score of 61.1, indicating that the internalization of work culture has not been fully achieved. This condition suggests the need to examine factors influencing employee performance, particularly competence and work discipline, with work motivation as a mediating variable. This study aims to analyze the direct and indirect effects of competence and work discipline on ASN performance through work motivation. This research employs a quantitative approach using a survey method. Data were collected from 360 ASN in the Malinau Regency Government using purposive sampling. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that competence does not have a significant direct effect on ASN performance. However, work discipline has a positive and significant effect on performance. Both competence and work discipline significantly influence work motivation, which in turn has a positive effect on performance. Furthermore, work motivation mediates the relationship between competence and performance, as well as between work discipline and performance. These findings highlight the important role of motivation in strengthening employee performance in the public sector.